Potential role of ixekizumab in the treatment of moderate-to-severe plaque psoriasis - Ren, Vicky (Dove Medical Press, 2013)
BACKGROUND: Psoriasis is a debilitating autoimmune skin disease that affects 2%–3% of the world’s population. Patients with moderate-to-severe plaque psoriasis suffer from a decreased quality of life as well as comorbidities. Newer biological agents have been shown to be more effective than traditional therapies. In this article, we assess the potential role of ixekizumab, an anti-interleukin (IL)-17 antibody, in treating moderate-to-severe plaque psoriasis. METHOD: We reviewed PubMed for articles regarding ixekizumab and the epidemiology and management of plaque psoriasis. RESULTS: In a Phase I clinical trial, treatment with ixekizumab resulted in both clinical and histopathologic improvement of psoriasis, which suggests that IL-17 may be a key driver in the pathogenesis of psoriasis. In a Phase II clinical trial, treatment with ixekizumab resulted in rapid clinical improvement of psoriasis, which lends further support to its role as an effective treatment for patients with chronic moderate-to-severe plaque psoriasis. Reductions in Psoriasis Area and Severity Index (PASI) score are comparable to those associated with currently marketed biologics. CONCLUSION: Literature concerning the effects of ixekizumab on chronic moderate-to-severe plaque psoriasis is currently limited to two clinical trials. Results suggest that ixekizumab shows great therapeutic promise. However, more large-scale and long-term trials are needed to establish safety and efficacy.